Islam, Tranformasi Sosial Ekonomi Dan Public Civility - Muhammad Muhammad (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2012)
Debating the function and role of religion in public civility development that lately arise indicated the rise of awareness about the importance of religious values in the lives of individuals and the public sector. The role and function of religion sterilized from the public, especially in concerning to the political life, economic development and other public sectors. This article aims to provide elaboration of the discourse of religion in building public civility. The first part of this article presents the ontology of religion, its role and function in personal and public life. The second section presents the values of Islam in building public civility, which historically constructed from the experience of the early success of the Islamic struggle in building the ideal type of state in Madinah. Next section presents historical construction of economic development which was loaded with the values of public civility that ever be a reference of modern society in building their economic and monetary system. This article is discusses Islamic civility that taken from classical Islam. These experience are expected to become functional in realizing the hopes of the majority community to build public civility. Finally, this article closes with a conclusion that contains a general ideas that are offered in view of the relation of religion (Islam) in building public civility.